Pelatihan Teknik Melukis Imajinatif bagi Guru SBdP dI SDN 10 Ganting dan SDN 31 Pasir Kandang Padang - Wikarya, Yusron; Sandra, Yofita; Wikarya, Rahmi Oktayory; Fitryona, Nessya; Eswendi, Eswendi; Wikarya, Fadhil Nugraha; Fahrezi, Fahmi Ade (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2024)
The priority problem consists of two aspects, namely: (1) the aspect of mastering the concept of imaginative painting techniques. (2) The aspect of applying imaginative painting techniques. The methods for solving the problem are: (1) model design, (2) counseling and discussion, (3) training. The end of the activity is expected to produce: (1) scientific publications in accredited national journals, (2) activity videos, and (3) publications in print/online media, (4) increased understanding of the concept of imaginative painting, and (5) increased imaginative painting skills. After the activity is completed, it has produced: (1) scientific articles published in accredited national journals, (2) activity videos published on YouTube, and (3) news articles published in print/online media, (4) increased understanding of the concept of at least 70% of the imaginative painting material mastered by participants, (5) Increased skills of at least each participant producing two imaginative paintings.